2020
DOI: 10.1016/j.radi.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in the radiology department: What radiographers need to know

Abstract: Objectives: The aim is to review current literature related to the diagnosis, management, and follow-up of suspected and confirmed Covid-19 cases. Key findings: Medical Imaging plays an important auxiliary role in the diagnosis of Covid-19 patients, mainly those most seriously affected. Practice differs widely among different countries, mainly due to the variability of access to resources (viral testing and imaging equipment, specialised staff, protective equipment). It has been now well-documented that chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 80 publications
1
88
0
4
Order By: Relevance
“… 21–25 In patient-facing environments, such as radiology departments, precautions to limit contamination between patients and/or other professionals in the management of suspected or confirmed COVID-19 patients, including strict adherence to a PPE protocol, is strongly advocated. 7,22,25 A large proportion of the RW (436/522; 83.6%) reported to have good knowledge of disease transmission, including the potential of cross-infection within the radiology department. This is broadly consistent with other studies 41–43 that similarly reported a higher understanding of infection prevention, control and compliance among healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 21–25 In patient-facing environments, such as radiology departments, precautions to limit contamination between patients and/or other professionals in the management of suspected or confirmed COVID-19 patients, including strict adherence to a PPE protocol, is strongly advocated. 7,22,25 A large proportion of the RW (436/522; 83.6%) reported to have good knowledge of disease transmission, including the potential of cross-infection within the radiology department. This is broadly consistent with other studies 41–43 that similarly reported a higher understanding of infection prevention, control and compliance among healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…Although strict adherence to these protocols (including increased PPE use and equipment decontamination) are fundamental for keeping both patients and the workforce safe. 7,21–25 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 Management of patients with known or suspected Covid-19 includes Medical Imaging (radiography and computed tomography (CT)). 8 As reported by Stogiannos and colleagues 9 practice varies widely within different countries, mainly due to differences in the access of resources (testing, imaging equipment, specialist staff and protective equipment).…”
Section: Introductionmentioning
confidence: 95%